HUMAN RIGHTS FOR FEMALE TERRORIST OFFENDERS: SUICIDE BOMBERS AND THEIR FAMILIES MEMBERS - Jenny Rahayu Afsebel Situmorang (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
ABSTRACTThis article shows a new perspective about female terrorist offenders, predominantly female suicide bombers. The method is a literature review with human rights and victim perspectives. The authors argue they are not indeed offenders in the terrorism and terror agenda, and even if they are lone offenders, they also have human rights. They are victims of power relations. How can female terrorist offenders, especially female suicide bombers and their families, get human rights? This article argues human rights ideas for them despite their position in society and legal as offenders or families of offenders. The victim and feminism perspectives use to support this idea. Female terrorist offenders include female suicide bombers who are still alive need protection in their daily lives, such as mental health and health access. [Artikel ini menunjukkan perspektif baru tentang perempuan pelaku terorisme terutama perempuan pelaku teror bunuh diri. Metode dalam penulisan menggunakan penelusuran literatur dengan penggunaan perspektif hak asasi manusia dan korban. Penulis menemukan bahwa mereka sebenarnya bukan pelaku sungguhan dalam terorisme maupun agenda teror, andai pun mereka pelaku independen, sebagai manusia mereka tetap punya hak asasi manusia. Mereka adalah korban relasi kuasa. Lantas, bagaimana perempuan pelaku terorisme secara khusus pelaku teror bunuh diri dan keluarganya mendapatkan hak asasi manusia? Artikel ini menggunakan pemikiran hak asasi manusia sebagai ide dan mengesampingkan posisi mereka sebagai pelaku maupun keluarga pelaku. Perspektif korban maupun feminis mendukung ide tersebut. Perempuan teroris termasuk perempuan pelaku teror bnuh diri yang masih hidup membutuhkan perlindungan dalam kehidupannya termasuk kesehatan mental maupun fisik.] Keyword: human rights, female suicide bombers, female terrorist, feminism, power relation